A Vowel Based Word Splitter to Improve Performance of Existing Nepali Morphological Analyzers on Words Borrowed from Sanskrit - Adhikari, Madhusudan (Kathmandu University Journal of Science, Engineering and Technology, 2020)
Nepali lexicon is rich in words borrowed from Sanskrit language, called "Tatsama" words. These words have a specific set of rules to split them into affixes and morphemes. This paper details these rules and describes an implementation that can be used to improve existing Nepali Morphological Analyzers which do not yet implement concrete rules for these kinds of words.